Optimal USB to Serial Converter and Delphi Software Integration for Emergency Call Handling - Marissa Widi Anggraini; Mohammad Luqman (PT. ELSHAD TECHNOLOGY INDONESIA, 2023)
This study focuses on evaluating the hardware and software integration performance in the context of an emergency call handling system. The aim is to test the efficiency of two main components, namely the USB to SERIAL converter and Delphi software, with a focus on serial data transmission and the software's ability to process position information from the emergency call sender module. The research method includes specific testing of both components. The test results indicate that the USB to SERIAL converter successfully transmits serial data without failure. The Delphi software also demonstrates optimal performance in reading, processing, and displaying position information through Google Maps. These results validate the overall integration of hardware and software, affirming that both function optimally. Reliable, fast, and accurate responses to emergency calls can be ensured, supporting the development of emergency handling technology. In conclusion, this research shows that efficient integration between the USB to SERIAL converter and Delphi software provides a solid foundation for improving the speed and efficiency of responses to emergency situations through the sophisticated combination of hardware and software.